Postpartum atypical haemolytic uremic syndrome: a rare case report - Khatod, Neha; Mukharjee, Shubhra; Malviya, Vijay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Hemolytic uremic syndrome (HUS) is characterized by triad of microangiopathic hemolytic anaemia, Thrombocytopenia and Acute renal failure. Genetically predisposed women develop HUS and may be triggered by pregnancy. The diagnosis is challenging due to overlapping clinical features of other diseases in pregnancy. The long-term prognosis is guarded. We are presenting a case of a young primigravida who underwent emergency lower (uterine) segment caesarean section (LSCS). She developed progressive anaemia, thrombocytopenia and renal failure postoperatively. Aggressive management with plasmapheresis, blood transfusions and hemodialysis saved her life. She is currently in remission.